PENGARUH PENGARUH INFRASTRUKTUR, BELANJA PARIWISATA, DAN INVESTASI DOMESTIK TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA - Siti Mardiyani; Izharudin (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to evaluate the impact of three main factors,[1] infrastructure, [2] tourism spending, and [3] domestic investment, on economic growth in Sumatra. Using secondary data from BPS and DJPK for the period 2010-2023, this research employs panel data regression analysis with the Fixed Effect Model (FEM). The findings indicate that simultaneously, these three variables significantly influence economic growth in Sumatra. Infrastructure and domestic investment variables have a negative and significant effect on economic growth, suggesting that despite the increase in infrastructure development, ineffective or uneven implementation may hinder economic growth. Meanwhile, the allocation of investments may not yet fully support productive sectors. On the other hand, tourism spending has a positive but insignificant effect, indicating that its contribution to economic growth remains limited. These findings highlight the importance of well-planned infrastructure development, improved effectiveness of domestic investments, and optimized tourism spending strategies to promote sustainable economic growth in Sumatra. This study recommends more integrated policies to enhance efficiency in infrastructure development and investment strategies, as well as to maximize the potential of the tourism sector in the region.